2007
DOI: 10.1124/jpet.107.120592
|View full text |Cite
|
Sign up to set email alerts
|

Nateglinide and Mitiglinide, but Not Sulfonylureas, Induce Insulin Secretion through a Mechanism Mediated by Calcium Release from Endoplasmic Reticulum

Abstract: Nateglinide and mitiglinide (glinides) are characterized as rapidonset and short-acting insulinotropic agents. Although both compounds do not have a sulfonylurea structure, it has been postulated that insulin secretion is preceded by their binding to Kir6.2/SUR1 complex, and a mechanism of insulin secretion of glinides has been accounted for by this pathway. However, we hypothesized the involvement of additional mechanisms of insulin secretion enhanced by glinides, and we analyzed the pattern of time course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Previous reports have shown that pancreatic islets and β-cell lines express functional RyR channels [ 9 ] that give rise to nuclear Ca 2+ signals [ 42 ]. To explore the presence of RyR channels in β-cells, previous studies have employed pharmacological tools [ 11 ], endogenous RyR ligands [ 16 , 19 , 43 ], detection of RyR mRNA levels [ 16 , 17 , 38 ] and protein [ 14 , 15 , 21 , 44 ], or quantitative determinations of ryanodine binding using fluorescently-labeled ryanodine [ 38 ]. Here, we confirmed that β-cells dissociated from pancreatic rat islets and MIN6 pancreatic β-cells express the RyR2 isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that pancreatic islets and β-cell lines express functional RyR channels [ 9 ] that give rise to nuclear Ca 2+ signals [ 42 ]. To explore the presence of RyR channels in β-cells, previous studies have employed pharmacological tools [ 11 ], endogenous RyR ligands [ 16 , 19 , 43 ], detection of RyR mRNA levels [ 16 , 17 , 38 ] and protein [ 14 , 15 , 21 , 44 ], or quantitative determinations of ryanodine binding using fluorescently-labeled ryanodine [ 38 ]. Here, we confirmed that β-cells dissociated from pancreatic rat islets and MIN6 pancreatic β-cells express the RyR2 isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Nateglinide binds the A‐site on SUR1 subunit while repaglinide binds the B‐site on both SUR1 and SUR2 subunits . In addition, glinides trigger intracellular Ca2+ release from the endoplasmic reticulum via ryanodine receptor activation, contributing to the enhancement of insulin secretion independently of KATP channel activity . However, long‐term exposure to glinides (as well as to SUs) accelerates KATP channel dysfunction and pancreatic β‐cell apoptosis and failure (“secondary failure”) over time …”
Section: Drugs and Bonementioning
confidence: 99%
“…Thus, sulfonylureas and cAMP co‐operatively activate Epac2A . In addition to closure of the β‐cell K ATP channels, nateglinide and mitiglinide have been shown to mobilize Ca 2+ from endoplasmic reticulum (ER) “Sulfonylureas except for gliclazide stimulate insulin secretion through activation of Epac2A in addition to closure of K ATP channels.”…”
Section: Signalling Mechanisms Of Sulfonylureas and Glinidesmentioning
confidence: 99%